Membangun Ketahanan Ekonomi Lokal: Program Pemberdayaan Bagi Pembudidaya Ikan di Kampung Buatan Baru, Kabupaten Siak - Arief, Hazmi; Amin, Bintal; Yanti, Chicka Willy; Metalisa, Rindi; Pebrian, Sispa; Abdurrahman, Ridwan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
The empowerment of fishing communities aims to increase capability, independence, and prosperity in the fisheries sector. Empowerment is part of efforts to strengthen the capacity of fish farmers and groups in Kampung Buatan Baru, Kerinci Kanan District, Siak Regency, Riau Province, in utilizing fishery resources sustainably, optimizing economic and social potential, and improving welfare. The objectives of this empowerment program are as follows: 1) Fish farmers can increase their capacity and skills; 2) Fish farmers can have access to fisheries resources; 3) Fish farmers can diversify their business in the fisheries sector. The empowerment activities for fish farmers are through direct counseling and demonstration plots for fish ponds. This activity will be carried out from June to August 2024. Activities include the socialization of empowerment programs, planning fisheries extension programs, implementing extension programs, monitoring programs, and evaluating programs. Measuring changes in the impact of this program was carried out by conducting pre-tests and post-tests on participants. The impact analysis results of this activity are changes in fish farmers' knowledge, attitudes, and skills in managing gourami and catfish cultivation businesses. Thus, assistance is needed for fish farmers so that the sustainability of cultivation businesses in Kampung Artificial Baru, Kerinci Kanan District, Siak Regency, Riau Province can be carried out well.